Data Mining as a Tool for Quality Assurance in HLIs : Experience from Dissertation Evaluation Process at UDSM (Asian Business Research, 2018)
This paper seeks to better understand how data mining can be used to improve quality assurance system in HLIs in Tanzania. A time series analysis of 133 pairs of examiners’ reports from the University of Dar es Salaam Business School (UDBS) was conducted. The analyses covered reports of three years from year 2014 to 2016. Analysis of means and correlation analysis were performed. In addition, content analysis of overall recommendations and comments provided by examiners was done. The results suggest that assessment reports contain useful information that could serve purpose other than awarding grades to students. The information contained could be used to inform future decisions geared to improving supervision, assessment and teaching in HLIs.